Effects of Humidity, Temperature and Bismuth Electrodeposition on Electroanalytical Performances of Nafion‐coated Printed Electrodes for Cd2+ and Pb2+ Detection. Issue 2 (26th September 2019) - Colozza, Noemi; Cacciotti, Ilaria; Moscone, Danila; Arduini, Fabiana
Abstract: The synergistic use of Nafion polymeric membrane and in situ electrodeposited bismuth film is a worthwhile strategy to develop electrochemical sensors for the detection of Cd 2+ and Pb 2+ . However, Nafion thin films morphological and conductivity properties have a strong dependence on the environmental conditions, such as relative humidity and temperature, while the bismuth in situ electroplating can affect the repeatability of measurements. With the aim to overcome these drawbacks, the effects of the storage environmental conditions were investigated to improve the morphological stability and electroanalytical performances of Nafion film‐based sensor for the detection of Cd 2+ and Pb 2+ . Nafion‐coated graphite‐based screen‐printed electrodes were stored at different humidity and temperature conditions and characterised by using square wave anodic stripping voltammetry, cyclic voltammetry, electrochemical impedance spectroscopy, and scanning electron microscopy. Significant differences were observed at the varying of humidity conditions, with an enhancement of sensor electrochemical performances at lower humidity. Furthermore, different approaches for bismuth in situ electrodeposition on Nafion‐coated screen‐printed electrodes were compared by using overlap or removal approach. This study disclosed considerable differences in the electrochemical performances and morphology of the resulting bismuth‐sensor, obtaining an enhancement of the working stability for the removal approach. Abstract :